As variedades da experiência antropocénica: crise climática, subjetividade e ontologia - António Carvalho (e-cadernos ces)
This article offers a provisional mapping of some of the affective impacts of the Anthropocene, a geological epoch proposed to illustrate the couplings of human agency and planetary phenomena. The article stems from two research projects: a PhD project which carried out an ontological analysis of Vipassana and Zen meditative practices in France, Portugal and the United Kingdom and a research project on the ontologies of the Anthropocene in Portugal, including semistructured interviews with members of the Transition Network. The paper explores three case studies which constitute heterogenous expressions of the varieties of anthropocenic experience: the suffering caused by the environmental and climate collapse; neoliberal environmentalism; and the ramifications of environmentalism and spirituality, supported by meditative phenomenologies.